Design directed self-assembly of donor–acceptor polymers. Issue 73 (21st July 2016) - Marszalek, Tomasz; Li, Mengmeng; Pisula, Wojciech
Abstract : This review discusses the role of chemical design on the self-assembly of donor–acceptor polymers on surfaces. Three major structural factors are highlighted including molecular weight, side chain engineering and backbone curvature of the polymers. Abstract : Donor–acceptor polymers with an alternating array of donor and acceptor moieties have gained particular attention during recent years as active components of organic electronics. By implementation of suitable subunits within the conjugated backbone, these polymers can be made either electron-deficient or -rich. Additionally, their band gap and light absorption can be precisely tuned for improved light-harvesting in solar cells. On the other hand, the polymer design can also be modified to encode the desired supramolecular self-assembly in the solid-state that is essential for an unhindered transport of charge carriers. This review focuses on three major factors playing a role in the assembly of donor–acceptor polymers on surfaces which are (1) nature, geometry and substitution position of solubilizing alkyl side chains, (2) shape of the conjugated polymer defined by the backbone curvature, and (3) molecular weight which determines the conjugation length of the polymer. These factors adjust the fine balance between attractive and repulsive forces and ensure a close polymer packing important for an efficient charge hopping between neighboring chains. On the microscopic scale, an appropriate domain formation with a low density of structural defects in the solution deposited thin film is crucial for the charge transport. The charge carrier transport through such thin films is characterized by field-effect transistors as basic electronic elements.